MORPHOPHYSIOLOGICAL AND PHOTOSYNTHETIC RESPONSES OF CORN GENETIC MATERIALS TO APPLICATION FORMS AND DOSES OF Azospirillum brasilense - Messias, Matheus; Valicheski, Romano Roberto; Peres, Mateus de Sousa; Lemes, Breno Caires Candido Pereira; De Jesus, Glaycon Erik Bernado Rodrigues; Lelis, Fellipy Viana; Coutrim, Everton Farias; Silva, Makcy Ramon Kened Souza (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
Brazil is the third largest maize-producing country in the world, despite having soils that are often acidic and have low nutrient reserves. However, the high cost of fertilizers generated the need for developing alternative technologies to reduce production costs. This work aimed to evaluate the effect of application methods and rates of Azospirillum brasilense on morphophysiological and photosynthetic parameters of maize genotypes. A randomized block experimental design was used, in a 4×4×2 factorial arrangement, with three replications. The parameters evaluated were chlorophyll contents; the fresh and dry weight of plant shoot components; root dry weight; culm diameter; root volume; leaf area; plant height; the number of developed leaves; initial, maximum, variable, and final fluorescence; and photochemical efficiency. Applying A. brasilense at rates of up to 200 mL ha-1 increased the total chlorophyll contents of leaves by 15.4% compared to the plants without inoculation. The maize variety SCS 156 presented higher shoot biomass production, regardless of inoculation, application method, or rate used; the varieties SCS 154 and SCS 155 presented significant increases in this parameter with the application of A. brasilense rates of up to 200 mL ha-1. Regarding the inoculant application methods, the variety SCS 155 presented better development when inoculated in the shoots. In contrast, the varieties SCS 155 and SCS 156 and the hybrid VIP 3 showed better growth when inoculated in the soil at planting.